Semi-automatic volumetric measurement of treatment response in hepatocellular carcinoma after trans-arterial chemoembolization - Budjan, Johannes; Lassel, Elke Angelika; Pilz, Lothar R.; Reichert, Miriam; Rathmann, Nils-Andreas; Diehl, Steffen J.; Schönberg, Stefan; Attenberger, Ulrike (Anticancer research, 2016)
Aim: To perform a quantitative, volumetric analysis of therapeutic effects of trans-arterial chemoembolization (TACE) in hepatocellular carcinoma (HCC) patients. Patients and Methods: Entire tumor volume and a subset of hypervascular tumor portions were analyzed pre- and post-TACE in magnetic resonance imaging datasets of 22 HCC patients using a semi-automated segmentation and evaluation tool from the Medical Imaging Interaction Toolkit. Results were compared to mRECIST measurements and inter-reader variability was assessed. Results: Mean total tumor volume increased statistical significantly after TACE (84.6 ml pre- vs. 97.1 ml post-TACE, p=0.03) while hypervascular tumor volume decreased from 9.1 ml pre- to 3.7 ml post-TACE (p=0.0001). Likewise, mRECIST diameters decreased significantly after therapy (44.2 vs. 15.4 mm). In the inter-reader assessment, overlap errors were 12.3-17.7% for entire and 36.3-64.2% for the enhancing tumor volume. Conclusion: Quantification of therapeutic changes after TACE therapy is feasible using a semi-automated segmentation and evaluation tool. Following TACE, hypervascular tumor volume decreases significantly.